Perinatal hypoxia as a risk factor for a more severe lexical-semantic deficit in children with developmental language disorder - Drljan, Bojana; Ječmenica, Nevena (Vojnosanitetski pregled, 2023)
Background/Aim. There is a small body of literature on the influence of perinatal hypoxia (PH) on language outcomes at a later age. Correspondingly, there are no studies on the influence of PH on the extent and severity of language deficits in children with developmental language disorder (DLD). The aim of this study was to examine the differences in lexical-semantic (LS) abilities in DLD children with the presence of PH (DLDph) and DLD children without any neurological risk factors (DLDwnrf). Methods. The study sample consisted of 96 children aged 5 to 8 years, divided into three groups: 25 children in the DLDph group, 30 children in the DLDwnrf group, and 41 typically developing (TD) peers. To compare age-related differences, an additional categorical variable was formed with two age groups – preschool and school-age children (5–6 and 7–8 years, respectively). LS abilities were investigated with specific measures for assessing the expressive vocabulary (EV) size, semantic processing (SP) skills, and lexical productivity (LPr). To assess LPr, measure for calculating lexical diversity from speech sample was applied. Results. Significant differences were observed between DLDph and DLDwnrf children on the SP assessment (p
Keywords: brain; hypoxia; language disorders; risk factors